Azithromycin Decreases Crevicular Fluid Volume and Mediator Content - Ho, W. (SAGE Publications, 2010)
Azithromycin enhances the response to root planing and produces anti-inflammatory effects in treating chronic lung disease. This led us to hypothesize that azithromycin inhibits inflammatory mediator production in gingiva, leading to decreased gingival crevicular fluid (GCF) volume. To test this hypothesis, ten periodontally healthy volunteers received azithromycin every 24 hours for 48 hours. GCF samples were collected from 12 maxillary interproximal sites prior to azithromycin (baseline) and 2, 4, 7, and 14 days later. Samples were assayed for IL-1β, IL-8, TNF-α, VEGF, IL-6, and IL-10. With azithromycin treatment, GCF volume decreased significantly on days 2 through 7 (P < 0.05), but increased toward baseline levels on day 14. This was accompanied by a transient decrease in the content of IL-1β, IL-8, TNF-α, and VEGF (P < 0.05). IL-6 and IL-10 were not detected. Since plaque was absent throughout the study, the findings suggest that azithromycin produces anti-inflammatory effects in gingiva.